A Rare Case Report of Isolated Tuberculous Caecal Perforation Presented as Acute Appendicitis - Lamture Y.R.1 , Gode Dilip2 , Aditya Mundada3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Koch’s abdomen is a common problem in India, with significant morbidity and mortality. Atuberculous caecal perforation without the involvement of adjacent ileum and ascending colon is very rare.Case Presentation: We report the case of a 23 years old man with clinical features of acute appendicitis.On laparotomy showed a caecal perforation with normal ileum, ascending colon and appendix. A caecalresection with end to end ileoascending anastomosis done. Histopathology confirms tuberculous granulomasof the caecum.Conclusions: We report this extremely uncommon case of caecal tuberculosis. This is very important as theincidence of tuberculosis is increasing in developing countries as well as developed.